IMPLEMENTASI KEARIFAN LOKAL NILAI KE- NU- AN DI SMP HASANUDDIN 06 SEMARANG - Damayanti, Alvina Dwi; Bisri, Kasan; Lestari, Prihatin (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2024)
This paper describes the implementation of local wisdom of Nu-an values as a school culture habit that aims to overcome the character and moral crisis. As an educational institution that has an important responsibility in educating based on formal education theory by not excluding character education. SMP Hasanuddin 06 Semarang develops local wisdom of NU values as a school program to realize the vision, mission, and goals of the school. The implementation of school culture is in accordance with the background of the institution that oversees the school. This research uses analytical qualitative method, with observation, interview and document techniques to collect data. There is a foundation and value that is formed by education based on NU an local wisdom. Steps in preparing habituation activities can facilitate activities in accordance with local potential.